TWO MANTLE SOURCES, TWO PLUMBING SYSTEMS: THOLEIITIC AND ALKALINE MAGMATISM OF THE MAYMECHA RIVER BASIN, SIBERIAN FLOOD VOLCANIC PROVINCE - Arndt N.; Chauvel C.; Czamanske G.; Fedorenko V. (My University, 1998)
Rocks of two distinctly different magma series are found in a ∼4000-m-thick sequence of lavas and tuffs in the Maymecha River basin which is part of the Siberian flood-volcanic province. The tholeiites are typical low-Ti continental flood basalts with remarkably restricted, petrologically evolved compositions. They have basaltic MgO contents, moderate concentrations of incompatible trace elements, moderate fractionation of incompatible from compatible elements, distinct negative Ta(Nb) anomalies, and Nd values of 0 to +2. The primary magmas were derived from a relatively shallow mantle source, and evolved in large crustal magma chambers where they acquired their relatively uniform compositions and became contaminated with continental crust. An alkaline series, in contrast, contains a wide range of rock types, from meymechite and picrite to trachytes, with a wide range of compositions (MgO from 0.7 to 38 wt%, SiO2 from 40 to 69 wt%, Ce from 14 to 320 ppm), high concentrations of incompatible elements and extreme fractionation of incompatible from compatible elements (Al2O3/TiO2∼1; Sm/Yb up to 11). These rocks lack Ta(Nb) anomalies and have a broad range of Nd values, from −2 to +5. The parental magmas are believed to have formed by low-degree melting at extreme mantle depths (>200 km). They bypassed the large crustal magma chambers and ascended rapidly to the surface, a consequence, perhaps, of high volatile contents in the primary magmas. The tholeiitic series dominates the lower part of the sequence and the alkaline series the upper part; at the interface, the two types are interlayered. The succession thus provides evidence of a radical change in the site of mantle melting, and the simultaneous operation of two very different crustal plumbing systems, during the evolution of this flood-volcanic province.